Food perception, lifestyle, nutritional and health status in the older people: Typologies and factors associated with aging well. (1st September 2021) - Maître, Isabelle; Sulmont-Rossé, Claire; Van Wymelbeke, Virginie; Cariou, Véronique; Bailly, Nathalie; Ferrandi, Jean-Marc; Salle, Agnès; Cardon, Philippe; Amand, Marion; Manckoundia, Patrick; Symoneaux, Ronan; Issanchou, Sylvie; et al.
Abstract: The aging process is associated with physiological, sensory, psychological, and sociological changes likely to have an impact on food intake and the nutritional status. The present study aimed to explore the heterogeneity of the French older population (>65 years old) using a multidisciplinary approach. More specifically, the study aimed to highlight different typologies (i.e. clusters of individuals with similar characteristics) within the older population. We conducted face-to-face interviews and tests with 559 French older people, recruited from different categories of dependency (at home without help, at home with help, in nursing homes). Clustering analysis highlighted seven clusters. Clusters 1–3 contained 'young' older people (<80) with a good nutritional status; these clusters differed according to food preferences, the desire to have a healthy diet, or interest in food. Clusters 4–7 mainly contained 'old' older people (80+), with an increase in the nutritional risk from cluster 4 to cluster 7. Two of these clusters grouped healthy and active people with a good level of appetite, while the two other clusters were associated with a clear decline in nutritional status, with people suffering from eating difficulties or depression. The results raise the need to develop targeted interventions to tackle malnutrition and implement health promotion strategies among the seniors.